P-380 Single-cell transcriptome analysis reveales that expression changes of the endometrium in repeated implantation failure are altered by HPV-mediated CXCL chemokine secretion. (30th June 2022) - Cao, C; Ruidi, Y; Ye, W; Ping, Z; Wendi, P; Xia, X; Yang, Y
Abstract: Study question: What are the mechanisms and molecular expression patterns of reduced endometrial receptivity in repeated implantation failure (RIF) after human papillomavirus (HPV) infection? Summary answer: The single-cell transcriptomic analysis identifies the expression changes of endometrium in RIF via HPV-mediated CXCL chemokines secretion in single-cell resolution. What is known already: Regardless of the advance of in vitro fertilization (IVF), RIF is still a formidable challenge for couples and physicians in clinical treatment. In infertile couples, a reduction in natural and assisted cumulative pregnancy rate and an increase in miscarriage rate are related to the HPV infection. Study design, size, duration: Cross-sectional clinical studies with 322 infertile couples undergoing IVF were integrated to demonstrate the associations between HPV infection and reproductive outcomes (pregnancy rate and miscarriage). Descriptive analysis of single-cell transcriptome data of uteruses, and transcriptome profiles of mid-secretory endometrium from 16 healthy fertile women and 38 repeated IVF failure women were analyzed to identify the expression patterns of endometrium in RIF. In vitro assays were used to validate the expression patterns in endometrium. Participants/materials, setting, methods: 322 infertile couples, single-cell transcriptome data of uteruses (human and mouse), and transcriptome profiles of endometrium (16 normal vs. 38 RIF) were used to analyze the association between HPV infection and reduced endometrial receptivity. HPV genes (E1, E2, E4, and E5) were transfected into a human normal endometrial epithelial cell line (hEM3), and immunohistochemistry, Westerns, quantitative PCR were used to validate the changes of CXCL chemokines in the endometrium in vitro . Main results and the role of chance: Integrated cross-sectional studies demonstrate that HPV+ women exhibit a decreased pregnancy rate (83.09%) as compared with HPV- women (55.17%, P  <0.001), and a higher miscarriage rate (62.5% vs. 16.7%, P  <0.001) and the relative risk of spontaneous abortion (odd ratio=2.84, P  <0.0001) were observed in HPV+ women. Transcriptome profiling analysis identified the enrichment of the processes related to viral protein interaction with cytokine and cytokine receptor and cytokine-cytokine receptor interaction, especially in the CXCL chemokine family. Further analysis of single-cell transcriptome demonstrated that the changed expression patterns were associated with endometrial epithelial cells and immune cells, including macrophage dendritic cells, monocytes, and granulocytes. Moreover, in vitro assays validated the HPV-mediated CXCL chemokines secretion, which played the role in recruiting immune cells. Limitations, reasons for caution: The current findings are based on the single-cell profiling analysis in normal endometrium. In addition, the in vivo response of the HPV infection may differ from the in vitro assay, which should be validated in the HPV infection couples. Wider implications of the findings: Our study demonstrated the expression changes of endometrium in RIF via HPV-mediated CXCL chemokines secretion, which provided insight into the mechanisms of HPV-induced reduced endometrial receptivity in single-cell resolution. Trial registration number: not applicable